Pendampingan Belajar Menulis Bahasa Indonesia, Menulis dan Membaca Tulis Al Quran Bagi Anak dan Remaja di Desa Batukarut dengan Metode Pembelajaran untuk Perbaikkan Prestasi dan Akhlak - Lalu Teguh Wardana; Rhifa Rahmadani; Agni Garib Mubarok; Siti Rohimah; Dinny Mardiana; Hidayat; Iwan Satriyo Nugroho (Politeknik Piksi Ganesha Indonesia, 2025)
Batukarut Village experiences problems regarding low basic literacy, lack of textual understanding of religion, lack of facilities and infrastructure, limited family support, and undirected community potential. The focus of community service is to increase the ability to write Indonesian at the elementary school (SD) level, increase the ability to read and write the Koran, develop interest in reading and writing, empower families and communities and strengthen character and cultural identity. The service method is Service Learning by implementing student learning under the guidance of lecturers. The results of service that have an impact on society are awareness of methods, motivation and consistency in learning to write Indonesian, write and read the Al-Quran for children and teenagers in Batukarut Village with learning methods to improve achievement and morals